Enhancing Teaching-Learning of Mathematics among Grade II Children Using Storytelling Strategy - Singh, Pooja Keshavan; Gandhi, Haneet (INDIAN EDUCATIONAL REVIEW, 2020)
This study is an action research aimed at enhancing mathematics learning of a low-participating class of Grade II learners to being more participating and getting engaged in doing mathematics. Storytelling proved to be an appropriate strategy for this involvement. Story-based on a popular animated series was adapted and concepts related to skip-counting were embedded into story situations. Anecdotes from the field included students’ verbal and written responses and pre-service teachers notes in their reflective journals. It was derived that the enhanced participation of Grade II children could be a result of the strong agency that the story fostered in the young learners, making them realise that their mathematical expertise was valuable and had serious implications for someone (the story characters).